ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN PERKAPITA DAN ANGKATAN KERJA TERHADAP TINGKAT KEMISKINAN ABSOLUTE DI KABUPATEN HULU SUNGAI UTARA - Muhammad Husien Erfani (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2019)
The purpose of this research is to know the Influence of Economic Growth,Perkapita Revenue, and Labor For Absolute Poverty Rate in Hulu Sungai Utara Regency in 2006-2015. Poverty is a cause of economic development where the dominant conditions are economic growth, per capita income, and labor force in Hulu Sungai Utara District. Time series data, and quantitative descriptive analysis using secondary data. By analyzing for 10 years using statistical test that is test R-squared (R2), simultaneous test (F test), partial test (T test) and Classic Assumption Test (Normality Test, Multikolinerity Test, Heteroskedasticity Test, Autocorrelation Test) assisted by program computer tools e-views 9.0. The influence of economic growth and the labor force does not have a significant effect on absolute poverty. The per capita income also has a significant effect on the absolute poverty level in Hulu Sungai Utara Regency. The most dominant factor influencing absolute poverty is per capita income.